CONCEPTUAL POLITICS - Yimaon, Chatchaphanu; กันต์โฉม, วรรณลดา (Thai Interdisciplinary and Sustainability Review, 2023)
This article aims to develop a Conceptual Politics that used a documentary research method for a period of 12 years to collect history and discipline in political science, concepts and theories in political science, teaching and learning in political science, and presenting the work of politics. The results of the study revealed that Political scientists should change their mindset from applying the political concept for explaining political phenomena to set the concept to be the work of politics. Political scientists then devised a plan or design a method, process, or create an outcome that enabled the learners happen to the work of politics or the “conceptual politics” in the minds of the learners.